Activin Receptor-Like Kinases: Structure, Function and Clinical Implications - Graham, Heather; Peng, Chun (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2006)
The transforming growth factor-β (TGF-β) superfamily regulates a multitude of cellular processes from fertilization to adulthood in vertebrates. Signaling by the TGF-β superfamily occurs via formation of heteromeric complexes consisting of type I and type II receptors. The type I receptors, referred to as activin receptor-like kinases (ALK), lie at the epicenter of the signaling cascade as they transduce TGF-β signals to intracellular regulators of transcription known as Smad proteins. Currently, seven ALKs have been identified in mammals. Structurally, ALKs possess an extracellular binding domain, a transmembrane domain, a GS domain that serves as the site of activation by type II receptors, and a kinase domain that activates downstream signaling molecules. ALKs mediate the effect of TGF-β superfamily on a variety of cellular processes such as proliferation, differentiation, apoptosis, adhesion and migration, and therefore play important roles in many biological processes. Some ALKs have been implicated in several disorders, including tumorigenesis, hemorrhagic telangiectasia (HHT), immune and renal diseases, and skeletal malfunctions, suggesting that these receptors can be used as drug targets.
Keywords: GS domain